Laparoscopic Pyloromyotomy for Congenital Hypertrophic Pyloric Stenosis: Our Experience with Twenty Cases - Ramji, Jaishri (Afr J Paediatr Surg, 2021)
PURPOSE: Laparoscopic pyloromyotomy for hypertrophic pyloric stenosis has become quite popular over the past decade. There have been many modifications in the technique initially described by Alain et al. in 1991. We describe our experience of the laparoscopic procedure performed in twenty cases. MATERIALS AND METHODS: This study includes twenty patients of pyloric stenosis who underwent laparoscopic pyloromyotomy from March 2017 to March 2020. All the infants had classical clinical symptoms and abdominal ultrasound confirming the diagnosis of pyloric stenosis. Two 3-mm ports and one 5-mm port were used. The duodenum was grasped to stabilise the olive; a stab knife cut to 10 mm and mounted on a needle holder was introduced through the 3-mm trocar in the left hypochondrium to perform the myotomy, and subsequently, the myotomy was spread with a 5-mm Maryland forceps. Feeding was started 6 h postoperatively. RESULTS: Twenty patients with congenital idiopathic pyloric stenosis underwent laparoscopic pyloromyotomy by this technique. The average operating time was 42 min. There were no peri- or post-operative complications. The post-operative hospital stay ranged between 36 h and 54 h. CONCLUSION: Laparoscopic pyloromyotomy using a stab knife mounted on a needle holder is a technically feasible, safe and effective surgical procedure for pyloric stenosis.